2020
DOI: 10.24251/hicss.2020.115
|View full text |Cite
|
Sign up to set email alerts
|

Data Acquisition and Processing for GeoAI Models to Support Sustainable Agricultural Practices

Abstract: There are growing opportunities to leverage new technologies and data sources to address global problems related to sustainability, climate change, and biodiversity loss. The emerging discipline of GeoAI resulting from the convergence of AI and Geospatial science (Geo-AI) is enabling the possibility to harness the increasingly available open Earth Observation data collected from different constellations of satellites and sensors with high spatial, spectral and temporal resolutions. However, transforming these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Examining AI in sustainable agriculture can be a potentially rich and important research stream in green IS (Nishant, Kennedy & Corbett, 2020), with implications for using and developing AI in other environmental and social contexts. While recognizing that well-developed knowledge around the design and use of IS undoubtedly has relevance to questions related to AI and other agricultural technologies (García Pereira, Ojo, Curry & Porwol, 2020;Ginige, Richards, Ginige & Hitchens, 2020;Newlands, Ghahari, Gel, Lyubchich & Mahdi,2019;Ofori & El-Gayar, 2020), we argue that the distinctive nature of AI necessitates new perspectives. Literature on the interaction between humans and AI (Tarafdar, Page, & Marabelli, 2022) suggests a continuous transformation of human knowledge (Grønsund & Aanestad, 2020;Raisch & Krakowski, 2020).…”
Section: Introductionmentioning
confidence: 87%
“…Examining AI in sustainable agriculture can be a potentially rich and important research stream in green IS (Nishant, Kennedy & Corbett, 2020), with implications for using and developing AI in other environmental and social contexts. While recognizing that well-developed knowledge around the design and use of IS undoubtedly has relevance to questions related to AI and other agricultural technologies (García Pereira, Ojo, Curry & Porwol, 2020;Ginige, Richards, Ginige & Hitchens, 2020;Newlands, Ghahari, Gel, Lyubchich & Mahdi,2019;Ofori & El-Gayar, 2020), we argue that the distinctive nature of AI necessitates new perspectives. Literature on the interaction between humans and AI (Tarafdar, Page, & Marabelli, 2022) suggests a continuous transformation of human knowledge (Grønsund & Aanestad, 2020;Raisch & Krakowski, 2020).…”
Section: Introductionmentioning
confidence: 87%
“…In the GIS context, deep learning models have been used for different purposes such as geospatial modelling, remotely sensed imagery processing, navigation, governance and societal, and agriculture. Specifically, the efficacy of one-dimensional convolutional neural networks over RF has been studied when exploiting the temporal and spectral dimensions of remotely sensed imagery in other parts of the world (García Pereira et al, 2020;Pereira et al, 2019Pereira et al, , 2021. Other studies have demonstrated the potential of Recurrent Neural Networks (RNNs) such as Long-Short Term Memory (LSTM) to classify multitemporal Synthetic Aperture Radar (Ienco et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of spatial science, artificial intelligence methods, data mining, and high-performance computing to extract information from big spatial data is known as geospatial artificial intelligence (GeoAI) (Gomez et al 2016, Li et al 2016, VoPham et al 2018. GeoAI opens up more possibilities for using earth observation data collected from various constellations of satellites and sensors with high spatial, spectral, and temporal resolution (Pereira 2020).…”
Section: Introductionmentioning
confidence: 99%